DETERMINANTS OF SHARIA STOCK INVESTMENT INTEREST AMONG GENERATION Z: EVIDENCE FROM ISLAMIC BUSINESS MANAGEMENT PERSPECTIVE IN BANDAR LAMPUNG - Vitto Arga Bintama; Weny Rosilawati; Is Susanto (Jurnal Dinamika Ekonomi Syariah, 2026)
This study aims to analyze the influence of investment knowledge, technological advances, and risk preferences on investment interest in Sharia stocks in Generation Z in Bandar Lampung city in the perspective of Islamic Business Management. The research methods used are quantitative approach with purposive sampling technique to 100 respondents, data collection through Likert scale questionnaire, and data analysis using SmartPLS through validity, reliability, and structural model testing. The results showed that investment knowledge, technological advances, and risk preferences have a positive and significant effect on investment interest in Islamic stocks either partially or simultaneously, with an R-square value of 0.838, which means 83.8% variation in investment interest can be explained by these three variables, so that strengthening investment literacy, utilization of digital technology, and risk preference management in line with Islamic Business Management Principles play an important role in increasing investment interest in Islamic stocks in Generation Z